Nectee fish meal plant - De Leon, Hector Jr (College of Engineering, 1967)
On the following pages is presented a report on a fish meal plant. This plant is designed to operate at a capacity of 10 tons of fish meal per day, with operation being semi-batch having three shifts per day. The method of production employed is solvent extraction, the solvent being isopropanol. This particular solvent serves the double purpose of extracting the fish oil and deodorizing the final product, fish meal. This process also makes use of as little equipment as possible, thereby requiring a small land area. The design on which this report was based has been modified to suit the raw material. In the original design, a battery of extractors in series was used, whereas in this design, one extractor is all that is required since the oil content of the fish is very small. The plant is to be situated in Talisay, Batangas, near seashore. Land area is one hectare to provide space for future expansion. Total fish requirement for one day is 57,200 pounds of fresh tulingan. Total fixed capital investment involved in the process is P3,287,976 while the operating cost at maximum production is P2,011,565. Sales at maximum production is P2,420,000 for a selling price of P.363 per lb. of fish meal. Prospects of the industry are bright since break even point occurs at a production rate of 3.19 tons per day (Aries and Newton). However, when this break even point is read from the graph, it occurs at 5.1 tons per day, which is also quite satisfactory, considering that the pay-out time is in 4.5 years time. Return on investment is 11.05 percent.